A solvent loss study for the application of solvent extraction processes in the pharmaceutical industry. (15th March 2022) - Li, Wen; Lu, Hiep Thuan; Doblin, Monika S.; Bacic, Antony; Stevens, Geoffrey W.; Mumford, Kathryn A.
Graphical abstract: Highlights: Methanol and ethanol with volume fraction in aqueous phase ≤ 0.8 v/v are preferred for use as modifiers in pharmaceutical LLE processes. MIBK and acetone are not suitable for pharmaceutical LLE processes in the presence of the modifiers. Green solvents such as d -limonene can replace VOCs in LLE processes as they maintain low modifier and solvent losses. Hanson's solubility theory and COnductor-like Screening MOdel - Segment Activity Coefficient (COSMO-SAC) modelling are valuable tools for preliminary solvent screening for LLE processes. Abstract: Liquid – liquid extraction (LLE) processes have been widely applied to extract active pharmaceutical compounds (APCs) from plant materials at both the laboratory and industrial-scale. The approach to modify the aqueous phase with small molecule organic modifiers has been used to increase the solubility of APCs in the aqueous phase. This work investigates the solvent loss for 18 LLE systems, including three aqueous phase modifiers (methanol, ethanol and acetone), three traditional volatile organic compounds (VOCs) solvents (xylene, methyl isobutyl ketone (MIBK) and n- heptane) and three green solvents ( d- limonene, α- pinene and p- cymene) with the aim of identifying the most suitable solvents for cannabinoid extraction from cannabis tissues. The solvent selection screening using COnductor-like Screening MOdel - Segment Activity Coefficient (COSMO-SAC) modelling was investigated. The loss of modifier into organic solvents generally increases as the original modifier concentration in aqueous solution increases. Methanol and ethanol are preferred for use in pharmaceutical LLE processes with volume fractions in organic phases at equilibrium of ≤ 0.02 v/v and ≤ 0.06 v/v, respectively. The organic solvent loss into the alcoholic aqueous phase at ≤ 0.8 v/v alcohol/water aqueous phase is negligible. MIBK and acetone are not suitable for pharmaceutical LLE processes with the presence of the modifier. Both Hanson solubility parameters (HSPs) and COSMO-SAC modelling show good agreement with the experimental outcomes.